HELIGMOSOMOIDES POLYGYRUS INFECTION CAN INHIBIT COLITIS THROUGH DIRECT INTERACTION WITH INNATE IMMUNITY - Hang, Long (2010)
Less developed countries have a low incidence of immunological diseases like inflammatory bowel disease (IBD), perhaps prevented by the high prevalence of helminth infections in their populations. In the Rag IL10−/− T cell transfer model of colitis, Heligmosomoides polygyrus (Hp), an intestinal helminth, prevents and reverses intestinal inflammation. This model of colitis was used to explore the importance of innate immunity in Hp protection from IBD. Rag mice briefly exposed to Hp before reconstitution with IL10−/− colitogenic T cells are protected from colitis. Exposure to Hp before introduction of IL10−/− and OT2 T cells reduced the capacity of the intestinal mucosa to make IFNγ and IL17 after either anti-CD3 mAb- or OVA-stimulation. This depressed cytokine response was evident even in the absence of colitis suggesting that the down-modulation in pro-inflammatory cytokine secretion was not just secondary to improvement in intestinal inflammation. Following Hp infection, dendritic cells (DCs) from the lamina propria (LP) of Rag mice displayed decreased expression of CD80 and CD86, and heightened expression of PDCA-1 and CD40. They were also less responsive to LPS, producing less IL12p40 and IL10. Also diminished was their capacity to present OVA to OT2 T cells. These experiments infer that Hp does not require direct interactions with T or B cells to render animals resistant to colitis. DCs have an important role in driving both murine and human IBD. Data suggest that phenotypic alternations in mucosal DC function are part of the regulatory process.